2022
DOI: 10.1128/mbio.02253-22
|View full text |Cite
|
Sign up to set email alerts
|

The Cryptococcus neoformans Flc1 Homologue Controls Calcium Homeostasis and Confers Fungal Pathogenicity in the Infected Hosts

Abstract: Cryptococcosis is a highly lethal infection with limited drug choices, most of which are highly toxic or complicated by emerging antifungal resistance. There is a great need for new drug targets that are unique to the fungus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 90 publications
0
10
0
Order By: Relevance
“…Calcineurin is a Ca 2+ -calmodulin-dependent phosphatase, which in C. neoformans is activated predominantly by heat stress, but also by exogenous Ca 2+ and cell wall stress ( 30 ). This leads to dephosphorylation of the transcription factor Crz1 and its translocation to the nucleus ( 30 , 44 ) to induce the expression of genes involved in cell wall integrity and response to oxidative stress ( 30 32 ). To further explore the connection between the PHO and calcineurin pathways, we investigated whether altering cellular P i affects the calcineurin activation response.…”
Section: Resultsmentioning
confidence: 99%
“…Calcineurin is a Ca 2+ -calmodulin-dependent phosphatase, which in C. neoformans is activated predominantly by heat stress, but also by exogenous Ca 2+ and cell wall stress ( 30 ). This leads to dephosphorylation of the transcription factor Crz1 and its translocation to the nucleus ( 30 , 44 ) to induce the expression of genes involved in cell wall integrity and response to oxidative stress ( 30 32 ). To further explore the connection between the PHO and calcineurin pathways, we investigated whether altering cellular P i affects the calcineurin activation response.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, transient receptor potential (TRP) channels were found among mammals, flies, worms, ciliates, Chlamydomonas and yeasts [ 45 ]. The TRP channels act as sensors for various stresses, including temperature, pH, osmolarity and nutrient availability [ 46 , 47 , 48 , 49 ]. The first calcium-permeable TRP, initially isolated from Arabidopsis thaliana , can be activated by hyperosmotic shock and, therefore, was named calcium-permeable stress-gated cation channel 1 (CSC1) [ 47 ], which includes the PenV protein of P. chrysogenum and CefP of A. chrysogenum [ 50 ].…”
Section: Calcium Signaling Pathway In Fungal Cellmentioning
confidence: 99%
“…The Yvc1 channel protein located on the tonoplast is a homologue of mammalian transient receptor potential (TRP) channel protein responsible for the release of Ca 2+ from the vacuole into the cytoplasm [ 10 , 51 , 52 ]. FLC was recently proposed as a member of the FLC family required for importing FAD into the endoplasmic reticulum, and it represent a conserved fungal gene family of integral membrane protein, spanning a TRP-like domain [ 49 , 53 ]. Some studies suggest FLC could act as either a calcium sensor or directly as a calcium channel [ 49 ].…”
Section: Calcium Signaling Pathway In Fungal Cellmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been found that these proteins not only possess Ca 2+ regulatory functions but also assume distinctive and significant roles in their respective species ( 22 25 ). In the opportunistic yeast pathogen Cryptococcus neoformans , Flc1, a homolog of FLC family proteins found in the genome of S. cerevisiae , has been postulated to be essential for regulating stress response and virulence ( 26 , 27 ). Additionally, the deficiency of Flc1 in C. neoformans leads to an abnormal distribution of chitin, the inhibition of vacuole fusion, and the disruption of autophagy ( 26 , 27 ).…”
Section: Introductionmentioning
confidence: 99%